2002
DOI: 10.1081/lpr-120004770
|View full text |Cite
|
Sign up to set email alerts
|

The Next Generation of Liposome Delivery Systems: Recent Experience With Tumor-Targeted, Sterically-Stabilized Immunoliposomes and Active-Loading Gradients

Abstract: Three topics are discussed. Enhanced anti-tumor efficacy of targeted doxorubicin-containing sterically-stabilized liposomes using an anti-beta1 integrin Fab' ligand. Use of tumor targeting with an internalizing ligand to improve the efficacy of a non-leaky cisplatin-containing sterically-stabilized liposome formulation. Formulation variables (remote-loading with dextran ammonium sulfate, rigid lipid bilayer) used to optimize in vivo performance of a liposomal camptothecin analog.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(29 citation statements)
references
References 2 publications
0
29
0
Order By: Relevance
“…Several studies have documented improved therapeutic efficacy of LTLs targeted against internalizing antigens or receptors compared to non-targeted liposomes [15,18,20,29,35]. Also, a recent study demonstrated that a Stealth ® liposomal formulation of cisplatin, which lacked efficacy in pilot clinical studies, gave good therapeutic results when delivered in an immunoliposome that was targeted to an internalizing antigen [19]. In other studies, LTLs did not show improved therapeutic efficacy over non-targeted liposomal drugs, which was attributed to the lack of internalization of LTLs into the cells [36,37].…”
Section: B Internalizing Versus Non-internalizing Antigensmentioning
confidence: 97%
See 1 more Smart Citation
“…Several studies have documented improved therapeutic efficacy of LTLs targeted against internalizing antigens or receptors compared to non-targeted liposomes [15,18,20,29,35]. Also, a recent study demonstrated that a Stealth ® liposomal formulation of cisplatin, which lacked efficacy in pilot clinical studies, gave good therapeutic results when delivered in an immunoliposome that was targeted to an internalizing antigen [19]. In other studies, LTLs did not show improved therapeutic efficacy over non-targeted liposomal drugs, which was attributed to the lack of internalization of LTLs into the cells [36,37].…”
Section: B Internalizing Versus Non-internalizing Antigensmentioning
confidence: 97%
“…The ligands promote the selective binding of the liposomes to tumor-associated antigens or receptors and facilitate the delivery of the drug-liposome packages to the cellular site of drug action. Targeting moieties can include: monoclonal antibodies (mAbs) or antibody fragments, peptides, growth factors, carbohydrates, glycoproteins, or receptor ligands [14][15][16][17][18][19][20][21][22][23][24][25].…”
Section: B Ligand-mediated Targetingmentioning
confidence: 99%
“…On the other hand, the coupling of targeting moieties to the surface of liposomes can promote the selective binding to achieve tissue specificity. Targeting moieties include monoclonal antibodies (mAbs) or antibody fragments, peptides, growth factors, carbohydrates, glycoproteins, or receptor ligands [116][117][118][119][120][121][122][123][124][125][126][127].…”
Section: Modified and Targeted Lipoplex Deliverymentioning
confidence: 99%
“…Antibody and their fragments are the most widely explored targeting moieties which can be easily anchored to liposomal surface without alteration of liposome integrity and the antibody properties (Torchilin, 1985). Immunoliposomes directed by monoclonal antibodies are promising vehicles for tumor targeted drug delivery (Abra et al, 2002;Kim et al, 2008). To further enhance the efficacy and cytosolic release of encapsulated content pH-sensitive immunoliposomes have been developed which are taken up by the target cell by ligand mediated endocytosis and upon internalization they fuses with the endosomal membrane at low pH.…”
Section: The Ph-sensitive Immunoliposomesmentioning
confidence: 99%